2020
DOI: 10.1155/2020/4504627
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prevalence, Associations ,Knowledge, and Practices about Diabetic Foot Disease in a Tertiary Care Hospital in Colombo, Sri Lanka

Abstract: Background. One in five adults in Sri Lanka has either diabetes or prediabetes, and one-third of those with diabetes are undiagnosed. Diabetic foot is a debilitating condition affecting up to 50% of patients with both type 1 and type 2 diabetes. The risk of nontraumatic lower limb amputations is 15 times higher in diabetic patients when compared with nondiabetics. Patient education about correct foot care practices is the cornerstone of prevention of diabetic foot disease. Objective. To assess the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…For example, a meta-analysis of foot care studies in Ethiopia reported a level of foot care practice at 64% ( Dagnew et al., 2021 ). Furthermore, higher levels of foot care are reported in countries such as Sri Lanka, and the Middle East, where Islam is the predominant religion and foot hygiene is part of the religious rituals ( Kaluarachchi et al., 2020 ). Common barriers to foot care practices for patients with diabetes include inadequate education on foot care, general neglect ( Pourkazemi et al., 2020 ), and the high cost of specialised footwear ( Kaluarachchi et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis of foot care studies in Ethiopia reported a level of foot care practice at 64% ( Dagnew et al., 2021 ). Furthermore, higher levels of foot care are reported in countries such as Sri Lanka, and the Middle East, where Islam is the predominant religion and foot hygiene is part of the religious rituals ( Kaluarachchi et al., 2020 ). Common barriers to foot care practices for patients with diabetes include inadequate education on foot care, general neglect ( Pourkazemi et al., 2020 ), and the high cost of specialised footwear ( Kaluarachchi et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes mellitus in the Sri Lankan urban population is estimated at 26.7% in 2019. 12 The national prevalence of COPD was estimated at 10.5% in 2017. 13 Therefore, the prevalence of diabetes and COPD in the study population was higher than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A body of research has underscored the adverse consequences associated with delayed diagnosis, including an elevated risk of infection, amputation, and mortality. [4][5][6][7][32][33][34] Within LMICs, investigations have consistently demonstrated that early identification of DFUs confers numerous advantages, encompassing higher healing rates, reduced amputation frequencies, decreased health care expenditures, and enhanced overall quality of life for affected individuals. [4][5][6][7] The contrast in mortality rates between LMICs and HICs further underscores the significance of early identification.…”
Section: Early Identification and Diagnosismentioning
confidence: 99%
“…Early detection and intervention can significantly improve wound healing, reduce the need for amputation, and improve the quality of life for individuals with DFUs 4,6,7 . However, the management strategies employed in LMICs for early DFUs may differ from those in high‐income countries (HICs) due to resource constraints and other contextual factors 5 …”
Section: Introductionmentioning
confidence: 99%